Individual Meropenem Clearance in Infants on ECMO and CVVHDF is Difficult to Predict: A Case Report and Review of the Literature. Issue 2 (February 2022) - Jabareen, Ali; Nassar, Laila; Karasik, Marina; Efrati, Edna; Hadash, Amir; Kassis, Imad; Kurnik, Daniel
Abstract : Objectives: Meropenem is a broad-spectrum carbapenem antibiotic with mostly renal excretion. Conflicting data are available regarding meropenem pharmacokinetics in critically ill neonates on concomitant continuous renal replacement therapy (CRRT) and/or extracorporeal membrane oxygenation (ECMO). Our objectives were to assess meropenem clearance in a neonate on CRRT and ECMO, compare it to previously published data and assess whether dose recommendations can be generalized in this population. Case description: A 2.5 kg male infant with a large diaphragmatic hernia was delivered by cesarean section at week 35 and immediately mechanically ventilated due to shock and respiratory insufficiency. He underwent surgical correction of the hernia, but developed recurrent sepsis, multiorgan failure and pulmonary hypertension. He remained mechanically ventilated and required ECMO and continuous venovenous hemodiafiltration. He was started on meropenem 40 mg/kg/dose, every 8 hs for Enterobacter cloacae bacteremia and sepsis, but due to lack of clinical and microbiologic response despite in vitro susceptibility, he was started on a continuous meropenem infusion of 240 mg/kg/d, based on dose recommendations in a similar case. We measured steady state meropenem plasma concentrations on 2 occasions, during ECMO and continuous venovenous hemodiafiltration (CVVHDF) and then on CVVHDF only. Results: Meropenem serum concentrations were 90 and 64 mg/L on the first and second occasion (therapeutic target concentration, 10 mg/L) corresponding to a clearance of 1.9 and 2.6 mL/kg/min. This clearance estimate was substantially lower than that reported in toddlers on CRRT and ECMO in some studies. Conclusion: In neonates and infants, meropenem clearance is difficult to predict because of dynamic ontogenetic changes in renal function. This problem is further aggravated in acutely ill infants with decreased renal function, renal replacement therapy and/or ECMO. Therefore, Target Concentration Intervention based on meropenem plasma concentrations is indispensable to ensure therapeutic exposure in this population.